An inventory model for parameter Weibull deterioration in trapezoidal demand under shortages. Issue 5 (2nd September 2016) - Mishra, Umakanta
Abstract: This present paper deals with an inventory model with two parameter Weibull deterioration and trapezoidal type demand rate when production and demand are time dependent. Two different EOQ, namely, (i) shortages are not allowed and (ii) shortages are allowed has been considered here. The practical execution of the aimed EOQ model is represented using numerical example. Sensitivity analysis is carried out to show the effect of changes in the parameters on the optimum solution.